SISTEM INFORMASI PEMULASARAN JENAZAH BERBASIS WEB (STUDI KASUS: RSUD INDRAMAYU) (Program Studi Teknik Informatika Universitas Muhammadiyah Cirebon, 2022)
National health development is aimed at increasing awareness, willingness and ability to live healthy for everyone in order to realize optimal health degrees as an element of general welfare as mandated in the Preamble to the 1945 Constitution of the Republic of Indonesia. So that the government is obliged to improve services. who is in the hospital. In this study, the authors created a website-based corpse information system to make it easier, faster and more efficient to return corpses. the author uses the PHP programming language, Codeigniter Framework and MySQL database and uses the R&D (Reasearch And Development) method in the research conducted, the author also uses DFD (Data Flow Diagrams) writing, namely Data Flow Diagrams, FlowMap, Flowcharts and Entity Realitionship diagrams (Erd) in compiling writing system design. The results of making this system can integrate each unit for the relocation of corpses, can provide information to the families of deceased patients. Keywords: Information Systems, relocation, corpses, return schedules, repatriation of bodies